Adaptation Experience Of Overseas Chinese Studyingin Guangxi Province Through ‘Chineseness’ Perspective In Higher Education Institutions - Li, Ying (2024)
Global student mobility in higher education has witnessed an emerging reverse trend as students flow back to their ancestral homeland country. Yet, the influences of this similar ancestral background on their reverse education experience remain to be addressed. Likewise, an increasing number of overseas chinese students are choosing to study in china rather than in traditional western destinations. At the same time, it is still underdetermined whether their shared chineseness roots and origins can provide them with a smooth adaptation experience in china. Given that the adaptation of international students studying in china’s higher education institutions from similar backgrounds and origins is under-explored, what influence of cultural similarity on adaptation in china is still to be resolved. Thus, this study sets out to investigate the adaptation experience of overseas chinese studying in china’s universities with a focus on their chineseness background. Specifically, it is designed to examine how their ethnic chinese background, namely chineseness, interplayed with their adaptation experience in china. This study has employed a qualitative research approach and case study method through semi-structured interviews with 20 southeast asian (sea) overseas chinese studying in china.